2017
DOI: 10.7717/peerj.3185
|View full text |Cite
|
Sign up to set email alerts
|

Meloxicam ameliorates the cartilage and subchondral bone deterioration in monoiodoacetate-induced rat osteoarthritis

Abstract: ObjectiveThis study aimed to quantify the cartilage- and subchondral bone-related effects of low-dose and high-dose meloxicam treatment in the late phase of mono-iodoacetate-induced osteoarthritis of the stifle.MethodsThirty-four male Wistar rats received intra-articular injection of mono-iodoacetate to trigger osteoarthritis; 10 control animals (Grp Co) received saline. The mono-iodoacetate-injected rats were assigned to three groups and treated from week 4 to the end of week 7 with placebo (Grp P, n = 11), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…Fourteen of the included studies have investigated chondroprotective actions of selective COX-2 inhibitors after systemic administration (Table 1). Most studies focused on chondroprotective actions of the selective COX-2 inhibitor celecoxib [12][13][14][15][16][17][18][19][20][21], while other studies investigated chondroprotective actions of meloxicam [22,23] and etoricoxib [24,25]. Four studies that investigated chondroprotective actions of selective COX-2 inhibitors in surgically induced OA models failed to demonstrate chondroprotective actions when the drug was administered directly after OA induction [12,14,18,22].…”
Section: Preclinical Studies: Oral and Intraperitoneal Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen of the included studies have investigated chondroprotective actions of selective COX-2 inhibitors after systemic administration (Table 1). Most studies focused on chondroprotective actions of the selective COX-2 inhibitor celecoxib [12][13][14][15][16][17][18][19][20][21], while other studies investigated chondroprotective actions of meloxicam [22,23] and etoricoxib [24,25]. Four studies that investigated chondroprotective actions of selective COX-2 inhibitors in surgically induced OA models failed to demonstrate chondroprotective actions when the drug was administered directly after OA induction [12,14,18,22].…”
Section: Preclinical Studies: Oral and Intraperitoneal Administrationmentioning
confidence: 99%
“…In conclusion, there is conflicting evidence regarding the chondroprotective actions of systemically administered selective COX-2 inhibitors since five studies did not show chondroprotective actions, while nine studies showed chondroprotective actions after systemic administration with selective COX-2 inhibitors. Next to surgically induced OA models, the monosodium iodoacetate (MIA) rat OA model [16,17,23], the collagenase OA model [13,19] and the spontaneous OA mouse model (STR/Ort) [21] were also used to investigate chondroprotective actions of selective COX-2 inhibitors celecoxib [13,16,17,19,21] and meloxicam [23]. In these studies, chondroprotective actions of selective COX-2 inhibitors were observed after oral administration as evidenced by improved histological scores compared to the controls.…”
Section: Preclinical Studies: Oral and Intraperitoneal Administrationmentioning
confidence: 99%
“…The use of meloxicam is increasing due to its high intrinsic activity. It is widely used in the treatment of osteoarthritis, rheumatoid arthritis and neurophatic pain in humans [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the drug could selectively modulate the expression of the glutamatergic signaling system components along the NMDA: AMPA receptor stoichiometry and repress glutamate excitotoxicity, leading to neuronal death. Meloxicam represses low-grade inflammation, even in non-vascularized tissues (126), and has a dual beneficial effect on extracellular matrix repair. Through its anti-fibrotic effect, downregulates the hydroxyproline production and collagen deposition, and it is angiostatic and anti-oxidant through stimulation of glutathione peroxidase, catalase, superoxide dismutase, and decrease of lipid peroxidation and myeloperoxidase activity (127,128).…”
Section: Experimental Evidence For Pharmacological Checkpoints Of Infmentioning
confidence: 99%